Copyright/Patent of Sihobuk Peanut Products Research Object One of the Sihobuk Peanut Businesses, Tarutung - Aldi Oktavianus barus; Antonio Mario Clarentiano Nababan; Jeremy Deo Girsang; Zakharia Sembiring (PT FORMOSA CENDEKIA GLOBAL, 2023)
Sihobuk peanuts are processed products from selected peanuts which are the best agricultural commodity from North Tapanuli district because they are influenced by fertile soil and good rainfall and are processed in the traditional way by the people of Sihobuk village so as to produce quality with a distinctive aroma that is different from other products. other similar types. This type of research is empirical juridical where the data source is obtained from primary legal materials, secondary legal materials and tertiary legal materials. Data collection was carried out through library research and field studies by conducting interviews. The data analysis used is qualitative data analysis. The results of this study indicate that sihobuk beans meet the requirements as a geographical indication product according to the Trademark and Geographical Indication Law. Sihobuk nuts will receive legal protection from geographical indications if they have been registered with the Directorate General of Intellectual Property Rights. The role of the local government in the registration of sihobuk beans is to provide assistance in facilitating the licensing process, to socialize Geographical Indications to business actors and to campaign for the need for registration of Geographical Indications. human resources who are experts in identifying products that have the potential to be used as geographic indications.